PENGARUH BUDAYA ORGANISASI, SISTEM PENGENDALIAN INTERNAL DAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this study is to test the influence of Organizational Culture, Internal Control Systems, and Information Technology on the Quality of Financial Statements. The study population was all employees of PT Solo Murni and a sample was taken, namely 42 employees in the financial division of PT Solo Murni.The data obtained was primary data obtained from the distribution of questionnaires with a total of 24 questions. Each question is measured by five likert scales. The data analysis technique in this study uses multiple linear regression analysis techniques. The results showed that the variables of Organizational Culture, Internal Control System, and Information Technology partially had a positive and significant effect on the Quality of Financial Statements. Simultaneously, Organizational Culture Variables, Internal Control Systems, and Information Technology have a significant effect on the Quality of Financial Statements. Keyword : Organizational Culture, Internal Control Systems, Information Technology , Quality of Financial Statements